Neck pain and dysphagia secondary to diffuse idiopathic skeletal hyperostosis of the cervical spine: A case report - Erdem Sultanoğlu, Tuba; Sultanoğlu, Hasan (Journal of Surgery and Medicine, 2019)
Diffuse idiopathicskeletal hyperostosis (DISH), also known as Forestier disease is characterizedby calcification and ossification of the soft tissues, mainly ligaments andentheses. DISH is a systemic non inflammatory disease of unknown cause and isconsidered an underdiagnosed and mostly asymptomatic nonprimary osteoarthritis.This condition is recognized radiologically only. Rarely, large projectinganterior osteophytes result in esophageal impingement and distortion leading todysphagia. We report the case of dysphagia and neck pain due to DISH of the cervicalspine in a 60 year old female. The patient came to the emergency departmentwith neck pain and dysphagia after falling.